A checklist of New Zealand Cerambycidae (Insecta: Coleoptera), excluding Lamiinae. Issue 2 (3rd July 2017) - Sopow, Stephanie L.; Bain, John
ABSTRACT: We provide a comprehensive list of species of Cerambycidae (Insecta: Coleoptera), excluding Lamiinae, known to be present in New Zealand. We also reinstate the following genera: Drotus, Epheus, Navomorpha, Pseudocalliprason and Stenopotes ; all of these are monotypic except for Navomorpha, which has four described species. Coptomma marrisi is tranferred to Navomorpha (new combination). Full synonymies are given for all species.